The relationship between sprinting speed, explosive jumping and grip strength in school children from the Western Cape. - van Wyk, Pieter Willem Schalk (Stellenbosch : Stellenbosch University, 2016)
Thesis (M Sport Sc)--Stellenbosch University, 2016